Combination of cyclooxygenase-2 inhibitor and doxorubicin increases the growth inhibition and apoptosis in human hepatocellular carcinoma cells - Pan, Y.Y.; Xu, S.P.; Jia, X.Y.; Xu, H.Q.; Zhang, Y.; Rui, L.X.; Wei, W. (Experimental Oncology, 2007)
Inhibition of cyclooxygenase (COX)-2 elicits therapeutic effects in solid tumors that are coupled with the inhibition of cell proliferation and induction of apoptosis in tumor cells. Aim: This study was designed to investigate the role of COX-2 inhibitor nimesulide in cell growth and apoptosis of the cultured human hepatocellular carcinoma HepG2 cells. Methods: We performed the MTT assay, flow cytometric analysis and cell morphology study to evaluate growth inhibition and cell apoptosis upon the action of nimesulide alone or along with doxorubicin, a common agent for the treatment of human hepatocellular carcinoma. Results: Our results showed that the treatment of HepG2 cells with more than 50 µM of nimesulide suppressed COX-2 enzyme activity because of reduced PGE2 production, and then induced growth inhibition and cell apoptosis despite no alterations of COX-2 protein expression. Importantly, the combination of 50 µM or 100 µM of nimesulide and low concentrations (5 µM to 20 µM) of doxorubicin resulted in enhanced cell growth inhibition, apoptosis induction and reduced VEGF production. Conclusion: These data suggest synergistic and/or additive effects of COX-2 inhibitors and chemotherapeutic agents, and may provide the rational for clinical studies of COX-2 inhibitors on the treatment or chemoprevention of human hepatocellular carcinoma. Угнетение циклооксигеназы-2 (ЦОГ-2) оказывает терапевтический эффект при лечении больных с солидными опухолями
и сопровождается снижением пролиферации опухолевых клеток и индукцией апоптоза. Цель: изучение роли ингибитора
ЦОГ-2 — нимесулида в процессах роста и апоптоза культивированных клеток гепатокарциномы человека HepG2.
Методы: для оценки апоптоза и угнетения роста клеток при применении нимесулида самостоятельно и в сочетании с
доксорубицином применяли MTT-анализ, проточную цитометрию и стандартные морфологические методы. Результаты:
установлено, что обработка клеток HepG2 cells нимесулидом в концентрации > 50 μM приводила к угнетению активности
ЦОГ-2 за счет снижения продукции PGE2
, после чего отмечали подавление роста и апоптоз клеток при неизмененном
уровне экспрессии ЦОГ-2. Комбинированное применение 50 μM или 100 μM нимесулида и доксорубицина в концентрации
5–20 μM обусловило усиленное угнетение роста клеток, индукции апоптоза и снижение продукции VEGF. Выводы:
полученные данные свидетельствуют о синергическом и/или аддитивном эффекте при применении ингибиторов ЦОГ-2
и химиотерапевтических препаратов.